If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25 + 2x = 32 + -1x Solving -25 + 2x = 32 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -25 + 2x + x = 32 + -1x + x Combine like terms: 2x + x = 3x -25 + 3x = 32 + -1x + x Combine like terms: -1x + x = 0 -25 + 3x = 32 + 0 -25 + 3x = 32 Add '25' to each side of the equation. -25 + 25 + 3x = 32 + 25 Combine like terms: -25 + 25 = 0 0 + 3x = 32 + 25 3x = 32 + 25 Combine like terms: 32 + 25 = 57 3x = 57 Divide each side by '3'. x = 19 Simplifying x = 19
| .07x+84532=x | | -94+x=81-6x | | (3x-1)=(5x-2) | | 136=Y(X*4-7) | | 4y=4x+2 | | 3(5x-4)-(3x+2)=16 | | 9x=5x+56 | | 4(t-2)+6t=5(2t+2)-9 | | 2x^2+3=-6x | | 9x=5x+55 | | 15-a+5a=5 | | 3x-4x=8-3 | | -7(2x-4)+5x=5(x+6) | | (x+4)=(2x+5) | | c=10-2.5 | | (x+5)=(x-9) | | y=10-2.5 | | -6(-4u+4)-5u=3(u-4)-2 | | 15-(-47)= | | 6(x-1)=-3(2-x)+3 | | -16t^2+128t+16.25=0 | | -6(y+2)=3y-9+3(2y+5) | | -x^2+3x+8=0 | | 3+7+6=2x+5+5x | | (-b^3)(d^2)=0 | | -4(v+1)=-6v-22 | | SolveV=lwhforH | | 3u-9=17(u-3) | | (4+x)+2= | | 650=0.3536x+14.857 | | 8(v+2)=-8v+32 | | 12log(e)(x)=33 |